Documentation of shared decision making around primary prevention defibrillator implantations. Issue 1 (25th December 2019) - Barakat, Amr F.; Asif, Anum; Inashvili, Ana; Szeto, Libby; Noor, Ahmed; Thalappillil, Alvin; Adhikari, Shubash; Fatima, Shumail; Pasupula, Deepak Kumar; Ahmad, Shahzad; Mathew, Don; Bhonsale, Aditya; et al.
Abstract: Introduction: Patients eligible for primary prevention implantable cardioverter‐defibrillator (ICD) therapy are faced with a complex decision that needs a clear understanding of the risks and benefits of such an intervention. In this study, our goal was to explore the documentation of primary prevention ICD discussions in the electronic medical records (EMRs) of eligible patients. Methods: In 1523 patients who met criteria for primary prevention ICD therapy between 2013 and 2015, we reviewed patient charts for ICD‐related documentation: "mention" by physicians or "discussion" with patient/family. The attitude of the physician and the patient/family toward ICD therapy during discussions was categorized into negative, neutral, or positive preference. Patients were followed to the end‐point of ICD implantation. Results: Over a median follow‐up of 442 days, 486 patients (32%) received an ICD. ICD was mentioned in the charts of 1105 (73%) patients, and a discussion with the patient/family about the risks and benefits of ICD was documented in 706 (46%) charts. On multivariable analyses, positive cardiologist (hazard ratio [HR]: 7.9, 95% confidence of intervals [CI]: 1.0‐59.7, P < .05), electrophysiologist (HR: 7.7, 95% CI: 1.9‐31.7, P < .001), and patient/family (HR: 9.9, 95% CI: 6.2‐15.7, P < .001) preferences toward ICD therapy during the first documented ICD discussion were independently associated with ICD implantation. Conclusions: In a large cohort of patients eligible for primary prevention ICD therapy, a discussion with the patient/family about the risks and benefits of ICD implantation was documented in less than 50% of the charts. More consistent documentation of the shared decision making around ICD therapy is needed.